1992
DOI: 10.1037/0003-066x.47.6.723
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in adolescent achievement: An ecological perspective.

Abstract: Using data collected from a large sample of high school students, the authors challenge three widely held explanations for the superior school performance of Asian-American adolescents, and the inferior performance of African- and Hispanic-American adolescents: group differences in (a) parenting practices, (b) familial values about education, and (c) youngsters' beliefs about the occupational rewards of academic success. They found that White youngsters benefit from the combination of authoritative parenting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
608
10
20

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 770 publications
(692 citation statements)
references
References 26 publications
39
608
10
20
Order By: Relevance
“…Although previous research has suggested that peer support is an especially important predictor for the academic success of African American adolescents (Steinberg, Dornbusch, & Brown, 1992), we found that the significance of peer support is particularly pronounced for African Americans exposed to multiple risks during early adolescence. In particular, we found that peer support was associated with higher math achievement test scores for adolescents with a greater number of risks, whereas peer support did not affect the math achievement test scores of adolescents with a fewer number of risks.…”
Section: Social Support Factorscontrasting
confidence: 96%
See 1 more Smart Citation
“…Although previous research has suggested that peer support is an especially important predictor for the academic success of African American adolescents (Steinberg, Dornbusch, & Brown, 1992), we found that the significance of peer support is particularly pronounced for African Americans exposed to multiple risks during early adolescence. In particular, we found that peer support was associated with higher math achievement test scores for adolescents with a greater number of risks, whereas peer support did not affect the math achievement test scores of adolescents with a fewer number of risks.…”
Section: Social Support Factorscontrasting
confidence: 96%
“…In particular, we found that peer support was associated with higher math achievement test scores for adolescents with a greater number of risks, whereas peer support did not affect the math achievement test scores of adolescents with a fewer number of risks. Although peer support for academic success may be limited for African American adolescents (Steinberg et al, 1992), our study suggests that African American adolescents exposed to multiple risks who perceive that they can depend on their peers for help with their personal and school difficulties may be more likely to experience higher academic outcomes than are their counterparts who perceive their peers as less supportive.…”
Section: Social Support Factorsmentioning
confidence: 73%
“…More preferred if one's goal is theory development are approaches that link ethnicity with the study of process, such as whether a particular set of relations is different in particular ethnic groups (see Rowe et al 1994). Ethnic differences in the relations between harsh parenting and childhood aggression (Deater-Deckard et al 1996) or between peer group influence and academic achievement (Steinberg et al 1992) are examples of studying ethnicity as a moderator of psychological process in the social domain.…”
Section: Implications For the Study Of Ethnicitymentioning
confidence: 99%
“…Finally, abundant evidence identifies a racial component to the gender gap, though its size (at least with respect to educational attainment) has changed considerably over time (DiPrete, McDaniel, Buchmann, and Shwed, 2009). Davis (2003) and Mandara (2006) draw attention to the large literature on the underachievement of black boys at all levels of education (see also Fan and Chen, 2001;Steinberg, Dornbusch, and Brown, 1992). Much of this literature is framed in terms of the presence or absence of an "oppositional culture" that differentially affects black youth, and particularly black males, though scholars disagree sharply as to whether black males experience more peer opposition to school effort than do white males either in general or in specific school contexts (Davis, 2003;Farkas, 1996;Farkas et al, 2002;Ainsworth-Darnell, 1998;Flashman, 2008).…”
mentioning
confidence: 99%